DE NOVO AND THERAPY-RELATED MYELODYSPLASTIC SYNDROMES: ANALOGIES AND DIFFERENCES: DE NOVO AND THERAPY-RELATED MYELODYSPLASTIC SYNDROMES - Leone, Prof. Giuseppe; Fabiani, Emiliano; Voso, Maria Teresa (Mediterranean Journal of Hematology and Infectious Diseases, 2022)
The aim of our review has been to give an appropriate idea of analogies and differences between primitive MDS (p-MDS) and t-MDS throughout an accurate reviewing of English peer-reviewed literature focusing on clinical, cytogenetic, epigenetic, and somatic mutation features of these two groups of diseases. Therapy-related MDS (t-MDS) are classified by WHO together with therapy-related acute myeloid leukemia (t-AML) in the same group, named therapy-related myeloid neoplasm. However, in clinical practice, the diagnosis of t-MDS is made with the same criteria as for primitive MDS (p-MDS), and the only difference is a previous non-myeloid neoplasm. The prognosis and the consequent therapy can be established following the same criteria as for p-MDS, and the therapy is generally decided using the same criteria. We stress the possible difference in cytogenetics, mutations, and epigenetics to distinguish the two forms. Actually, there is no marker specific for t-MDS either in cytogenetics, epigenetics, or mutations; however, some alterations are also frequent in t-MDS and, in general, they induce a poorer prognosis. So, the high-risk forms in t-MDS are prevalent. The present literature data suggest classifying the t-MDS as a subgroup of MDS and introducing some parameters to evaluate the probability of previous therapy in inducing MDS. An important issue remains the patient’s fitness, which strongly influences the outcome. Keywords: MDS, t-MDS- Cytogenetics, Mutation, Epigenetics.